Contemporary factors shaping the professional identity of occupational therapy lecturers - O’Shea, John; McGrath, Simon (Sage, 2018)
Introduction The contemporary factors of neoliberalism and evidence based practice (EBP) have implications for professional autonomy and values, education and training, ways of working and construction of knowledge. Occupational therapy lecturers are at the interface between student education and professional practice and therefore have unique insights into the way in which these factors are shaping their professional identity and that of the profession. Method Nine narrative inquiry focused interviews of occupational therapy lecturers from two universities were carried out. Data was interpreted through a Bourdieusian lens, of professional habitus, and analysed thematically. Findings The main factors influencing occupational therapy lecturer identity were noted to be relationships between professional identity and artistry; the professional body of knowledge and language; evidencing practice, neoliberalism and changes to teaching and learning. Conclusion 2 The structural factors of neoliberalism, EBP and associated policies are influencing the occupational therapy professional habitus and in turn occupational therapy lecturers’ professional identity. An effective critique of these structural factors is required to maintain the profession’s values and artistry and the knowledge upon which occupational therapy lecturers’ identity is formed and their approaches to teaching and learning are based.